Shadow - Robson, Mark, 1966- (London : Simon and Schuster, 2009)
Dragonrider Pell's flying skills, courage, and resourcefulness are put to the test as he and his night dragon, Shadow, race against power-hungry Segun to find the dark orb that will help save the leader of all dragonkind.
6.1
3-6
3-6
Keywords: Dragons -- Juvenile fiction; Dragons -- Fiction; Fantasy; Dragons -- Fiction; Fantastic fiction; Fantastic fiction